PROPHET – JESTER – LEGEND: AUTHOR’S TRAJECTORY OF ANATOL SYS - Kowalow, Siergiej (Porównania, 2019)
The article is dedicated to a complicated trajectory of the outstanding Belarusian poet Anatol Sys (1959-2005), whose unusual fate intrigues readers no less than his poetry, and makes researchers search for new explanations of metamorphoses in his life and creative work. From the memoirs of contemporaries, academic articles and works of art an extremely controversial image of the writer arises: a leader of the generation, a fighter with Communist ideology, a prophet of the national revival, a Genius; a disgusting poet, a jester, an alcoholic, a freak, a boor. There have been various assessments of Sys’s personality and the place of his work in the history of the Belarusian literature which “in the opinion of the author, originate for the following three reasons: 1) the extraordinary and contradictory nature of the poet; 2) the nature of the interval the time in which Sys lived and which falls into three epochs: stagnant Soviet (before 1984), transition-renaissance (1985-1992), and Lukashenko’s (since 1994); 3) a complex trajectory of the poet’s life and creative path which can be divided into three stages: initial, revival and Bohemian (“infernal”). Even during his life, the personality of Anatol Sys began to acquire myths and legends, and after his death, his best works entered the canon of the national literature of the 20th century.